Pottery Regions in Noricum: Evidence for Communities of Practice? - Auer, Martin (Rei Cretariae Romanae Fautorum Acta, 2022)
In this paper the pottery production in Noricum is examined based on the data about pottery regions in this area created during the author’s PhD work. Using different attributes of the vessels, the paper aims to explain intraregional equality and variability within different communities of potters. This approach is suggested by the occurrence of morphologically and stylistically equal vessels in different regions, which show distinct differences regarding the technology used to create them. The processes of knowledge transfer which can be traced through the spatial analysis of certain pottery attributes are compared with ethno archaeological data to gain new insights into the manufacturing process and its social embedment.